Impact of Azithromycin-Based Extended-Spectrum Antibiotic Prophylaxis on Noninfectious Cesarean Wound Complications - Ausbeck, Elizabeth B.; Jauk, Victoria C.; Boggess, Kim A.; Saade, George R.; Longo, Sherri; Clark, Erin A. S.; Esplin, Sean; Cleary, Kirsten; Wapner, Ronald; Letson, Kellett; Owens, Michelle; Abramovici, Adi; Ambalavanan, Namasivayam; Szychowski, Jeff M.; Andrews, William; Tita, Alan T. N.; for the Cesarean Section Optimal Antibiotic Prophylaxis Trial Consortium (American Journal of Perinatology, 2019)
Objective Adding azithromycin to standard antibiotic prophylaxis for unscheduled cesarean delivery has been shown to reduce postcesarean infections. Because wound infection with ureaplasmas may not be overtly purulent, we assessed the hypothesis that azithromycin-based extended-spectrum antibiotic prophylaxis also reduces wound complications that are identified as noninfectious.Study Design This is a secondary analysis of the C/SOAP (Cesarean Section Optimal Antibiotic Prophylaxis) randomized controlled trial, which enrolled women with singleton pregnancies ≥24 weeks who were undergoing nonelective cesarean. Women were randomized to adjunctive azithromycin or identical placebo up to 1 hour preincision. All wound complications occurring within 6 weeks were adjudicated into infection and noninfectious wound complications (seroma, hematoma, local cellulitis, and other noninfectious wound breakdown). The primary outcome for this analysis is the composite of noninfectious wound complications.Results At a total of 14 sites, 2,013 women were randomized to adjunctive azithromycin (n = 1,019) or placebo (n = 994). Groups were similar at baseline. Although there was a lower rate of noninfectious wound complications in the azithromycin group compared with placebo (2.9 vs. 3.8%), this was not statistically significant (p = 0.22).Conclusion While adding azithromycin to usual antibiotic prophylaxis for nonelective cesarean delivery does reduce the risk of postcesarean infections, it did not significantly reduce the risk of postcesarean noninfectious wound complications.
Keywords: cesarean; azithromycin; noninfectious wound; infection; wound complication